2015
DOI: 10.1182/blood-2014-10-551465
|View full text |Cite
|
Sign up to set email alerts
|

How I treat mixed-phenotype acute leukemia

Abstract: Mixed-phenotype acute leukemia (MPAL) encompasses a heterogeneous group of rare leukemias in which assigning a single lineage of origin is not possible. A variety of different terms and classification systems have been used historically to describe this entity. MPAL is currently defined by a limited set of lineage-specific markers proposed in the 2008 World Health Organization monograph on classification of tumors of hematopoietic and lymphoid tissues. In adult patients, MPAL is characterized by relative thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
152
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(158 citation statements)
references
References 68 publications
1
152
1
4
Order By: Relevance
“…The published data suggest poor treatment outcomes, in terms of both the probability of achieving complete remission and overall survival (OS), as compared with AML or ALL (ref. 19,25 ). A study of treatment in 35 children with MPAL meeting the EGIL criteria showed results comparable to those in AML but worse overall survival than in pediatric ALL (ref.…”
Section: Prognostic Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…The published data suggest poor treatment outcomes, in terms of both the probability of achieving complete remission and overall survival (OS), as compared with AML or ALL (ref. 19,25 ). A study of treatment in 35 children with MPAL meeting the EGIL criteria showed results comparable to those in AML but worse overall survival than in pediatric ALL (ref.…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…Therapy for Ph1+ MPAL is based on an ALL protocol adjusted to the patient's age, combined with TKI and followed by allogeneic HCT (ref. 25 ). In patients with Ph1+ ALL, excellent short-term outcomes were achieved using dasatinib combined with corticosteroids and intrathecal chemotherapy 30 .…”
Section: Treatment Of Mpalmentioning
confidence: 99%
See 3 more Smart Citations